Application opportunity of Doppler ultrasound combined with CT angiography in diabetic lower extremity arterial disease and the analysis of the risk factors - Zhang, ShaoRui; Wu, Yan; Guo, YuQing; Jia, XinJu; Kang, Yan; Shen, XueLian; Song, Jia; Yang, AiGe (Frontiers in Endocrinology, 2024)
Objective: This study examined the potential of combining Doppler ultrasound (DUS) and CT angiography (CTA) for early detection and intervention of lower extremity arterial disease (LEAD) in diabetes.Concurrently, risk factors influencing LEAD progression were analyzed. Methods: 106 Type-2 diabetes patients with LEAD, having undergone DUS and CTA, were divided into four stages according to Fontaine stage. Results of DUS and CTA were compared across stages and potential risk factors were analyzed. Results: Positive detection rates of LEAD differed between DUS and CTA for Fontaine stages I and II (P < 0.05), with no significant difference for stages III and IV (P > 0.05). CTA identified subgroups with mild to moderate stenosis and severe stenosis or occlusion, with positive rates on DUS of 17.95% and 89.9% respectively. Hypertension was found as an independent risk factor affecting LEAD progression. Conclusions: CTA should be performed early for LEAD in diabetes patients at Fontaine stages I and II, regardless of DUS results. For diabetes patients with LEAD, stringent blood pressure control is crucial to delay disease progression.